Cathepsin-L can resist lysis by human serum in Trypanosoma brucei brucei. - Sam Alsford; Rachel B Currier; José Afonso Guerra-Assunção; Taane G Clark; David Horn (PLoS Pathogens)
Closely related African trypanosomes cause lethal diseases but display distinct host ranges. Specifically, Trypanosoma brucei brucei causes nagana in livestock but fails to infect humans, while Trypanosoma brucei gambiense and Trypanosoma brucei rhodesiense cause sleeping sickness in humans. T. b. brucei fails to infect humans because it is sensitive to innate immune complexes found in normal human serum known as trypanolytic factor (TLF) 1 and 2; the lytic component is apolipoprotein-L1 in both TLFs. TLF resistance mechanisms of T. b. gambiense and T. b. rhodesiense are now known to arise through either gain or loss-of-function, but our understanding of factors that render T. b. brucei susceptible to lysis by human serum remains incomplete. We conducted a genome-scale RNA interference (RNAi) library screen for reduced sensitivity to human serum. Among only four high-confidence 'hits' were all three genes previously shown to sensitize T. b. brucei to human serum, the haptoglobin-haemoglobin receptor (HpHbR), inhibitor of cysteine peptidase (ICP) and the lysosomal protein, p67, thereby demonstrating the pivotal roles these factors play. The fourth gene identified encodes a predicted protein with eleven trans-membrane domains. Using chemical and genetic approaches, we show that ICP sensitizes T. b. brucei to human serum by modulating the essential cathepsin, CATL, a lysosomal cysteine peptidase. A second cathepsin, CATB, likely to be dispensable for growth in in vitro culture, has little or no impact on human-serum sensitivity. Our findings reveal major and novel determinants of human-serum sensitivity in T. b. brucei. They also shed light on the lysosomal protein-protein interactions that render T. b. brucei exquisitely sensitive to lytic factors in human serum, and indicate that CATL, an important potential drug target, has the capacity to resist these factors.